2019 IEEE/ACM 1st International Workshop on Software Engineering for Healthcare (SEH) 2019
DOI: 10.1109/seh.2019.00011
|View full text |Cite
|
Sign up to set email alerts
|

Blockchain: A Panacea for Electronic Health Records?

Abstract: Healthcare systems have been supported by technology to help improve the user experience with the entire health system. However, many operational challenges still remain, in particular those related to a unified management of electronic health records (EHR) that could enable multiple doctors to have access to the complete health history of their patient. Blockchain could support unified records, data security and privacy improvement and insurance decisions/transactions making it an effective solution for the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 11 publications
0
20
0
2
Order By: Relevance
“…Most databases store data and regulate access in a centralized fashion, which constitutes a weak point for security breaches as frequently reported in the US [125]. Methods that rely on decentralized networks, such as blockchain, have been suggested to provide additional security and data ownership for individuals [126][127][128]. However, as with all data security measures, there remains a trade-off between affordable protection and making data sufficiently accessible to researchers.…”
Section: Discussionmentioning
confidence: 99%
“…Most databases store data and regulate access in a centralized fashion, which constitutes a weak point for security breaches as frequently reported in the US [125]. Methods that rely on decentralized networks, such as blockchain, have been suggested to provide additional security and data ownership for individuals [126][127][128]. However, as with all data security measures, there remains a trade-off between affordable protection and making data sufficiently accessible to researchers.…”
Section: Discussionmentioning
confidence: 99%
“…For several years, healthcare has been considered an area with high potential for blockchain application. Potential uses include storing, sharing, and exchanging medical data using various access control strategies [3,14]. For example, Agbo et al [15] identified some crucial application areas, such as electronic medical records (EMRs), drug/pharmaceutical supply chains, biomedical research and education, remote patient monitoring (RPM), health insurance claims, and health data analytics (HDA).…”
Section: Blockchain In Healthcarementioning
confidence: 99%
“…Although many of the the World Health Organization's (WHO) systems 9 and a numerous number of global regulations (e.g., Drug Supply Chain Security Act (DSCSA) 10 ) were designed to help on the protection of integrity of the medication supply chain by gathering data at each step of a medication's journey, the global trade in counterfeit medicines continues to be robust with remarkable risks to general public. Counterfeit drugs could contain inactive ingredients, incorrect dosage of active ingredients and/or potential contaminants causing possible adverse allergic reactions [61].…”
Section: Medical Supply Chainmentioning
confidence: 99%
“…While we presented an initial view from the review in short papers [9], [10] focusing only on the usage of blockchain in managing the healthcare records, this paper presents the extended results from the review along with the complete set of mappings and process descriptions.…”
Section: Introductionmentioning
confidence: 99%